Shielding of hepatitis B virus-like nanoparticle with poly(2-ethyl-2-oxazoline) - Fam, See Yee; Chee, Chin Fei; Yong, Chean Yeah; Ho, Kok Lian; Abdul Razak, Mariatulqabtiah; Lau, Han Yih; Tan, Wen Siang (MDPI, 2019)
Virus-like nanoparticles (VLNPs) have been studied extensively as nanocarriers for targeted drug delivery to cancer cells. However, VLNPs have intrinsic drawbacks, in particular, potential antigenicity and immunogenicity, which hamper their clinical applications. Thus, they can be eliminated easily and rapidly by host immune systems, rendering these nanoparticles ineffective for drug delivery. The aim of this study was to reduce the antigenicity of hepatitis B core antigen (HBcAg) VLNPs by shielding them with a hydrophilic polymer, poly(2-ethyl-2-oxazoline) (PEtOx). In the present study, an amine-functionalized PEtOx (PEtOx-NH2) was synthesized using the living cationic ring-opening polymerization (CROP) technique and covalently conjugated to HBcAg VLNPs via carboxyl groups. The PEtOx-conjugated HBcAg (PEtOx-HBcAg) VLNPs were characterized with dynamic light scattering and UV-visible spectroscopy. The colloidal stability study indicated that both HBcAg and PEtOx-HBcAg VLNPs maintained their particle size in Tris-buffered saline (TBS) at human body temperature (37 °C) for at least five days. Enzyme-linked immunosorbent assays (ELISA) demonstrated that the antigenicity of PEtOx-HBcAg VLNPs reduced significantly as compared with unconjugated HBcAg VLNPs. This novel conjugation approach provides a general platform for resolving the antigenicity of VLNPs, enabling them to be developed into a variety of nanovehicles for targeted drug delivery.